PUSAT PERTUMBUHAN EKONOMI DAN INTERAKSI SPASIAL: STUDI EMPIRIS DI PROVINSI SUMATERA SELATAN - Purnomo, Sodik Dwi; Wahyuni, Yulina Tri; Danuta, Krisnhoe Sukma; Jati, Damar; Achadi, Ady (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
In 2010 and 2020, South Sumatra Province had the third highest GRDP on the island of Sumatra. However, based on the Williamson index, the level of income distribution that occurs between districts/cities is still low. This study aims to identify growth centers and spatial interactions of districts/cities in South Sumatra Province in 2010 and 2020.The analyses used in this research are scalogram analysis, centrality index and gravity analysis. The results showed that in 2010 there were 2 regencies/cities in Hierarchy I, 6 regencies/cities in Hierarchy II, 5 regencies/cities in Hierarchy III and 2 regencies/cities in Hierarchy IV. In 2020 there are 4 districts/cities in Hierarchy I, 4 districts/cities in Hierarchy II, 6 districts/cities in Hierarchy III and 1 district/city in Hierarchy IV. From 2010 to 2020, the interaction between growth centers and their hinterlands has increased. Banyuasin, Ogan Komering Ilir and Ogan Ilir districts are the areas that have the strongest interaction. The policy implication is that economic cooperation needs to be carried out between the growth center regions and the regions behind them so that economic growth can be assisted in each region.